(untitled) (Bangladesh Journal of Medical Science, 2014)
Objective: To find out the growth in the exclusively breastfed babies of the affluent mothers and to compare the figures with those of the children in the industrialized countries. Methods and materials: Fifty-three babies were selected in 1 year time period for this cross-sectional study under 6-month of age with prefixed criteria, such as exclusively breastfed and not fed with any formula feeding. Recommended schedule of immunization (EPI) was followed to weigh and measure for supine length. Data were analyzed in PC through SPSS and some calculations were done in calculator too. Place and time of work: Data were collected from August 2011 to June 2012 in the Pediatrics Department of Bangladesh Medical College Hospital and the Researchers Chamber at Dhanmondi, Dhaka. Results: The data of developed countries showed that in first 3-month of age, children grow in weight 30 gm/day and in length 3.5 cm/month, followed by weight gain of 20 gm/day and linear growth 2 cm/month in next 3-6 months. Our babies could be compared to those figures, with 33.54 gm/day in the weight gain and 4.17 cm/month in linear growth in the first 3 months. The average weight gain during the next 3 months (3-6 months of age) was 22.3 gm/d and linear growth for this period was 2.12 cm/month. Conclusion: Babies of our country in well-off families can grow optimally in comparison to the growth of the babies in the industrialized countries, or even can exceed, if they are exclusively breastfed and brought up ensuring immunization and follow up in educated mothers. DOI: http://dx.doi.org/10.3329/bjms.v13i4.20627 Bangladesh Journal of Medical Science Vol.13(4) 2014 p.466-469